2015
DOI: 10.5935/1678-9741.20150005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of remote ischemic postconditioning inflammatory changes in the lung parenchyma of rats submitted to ischemia and reperfusion

Abstract: ObjectiveTo assess the effects of postconditioning remote in ischemia-reperfusion injury in rat lungs.MethodsWistar rats (n=24) divided into 3 groups: GA (I/R) n=8, GB (R-Po) n=8, CG (control) n=8, underwent ischemia for 30 minutes artery occlusion abdominal aorta, followed by reperfusion for 60 minutes. Resected lungs and performed histological analysis and classification of morphological findings in accordance with the degree of tissue injury. Statistical analysis of the mean rating of the degree of tissue i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 11 publications
3
16
0
Order By: Relevance
“…The authors performed aortic clamping for 30 minutes and reperfusion for 60 minutes, with three cycles of IPC lasting two minutes each. In this study, IPC performed with the same time span used by Dorsa et al [15] did not result in hepatic protection, obtaining results similar to the I/R group. However, there is still a lot of controversy in the literature on the outcome of remote protection of IPC.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…The authors performed aortic clamping for 30 minutes and reperfusion for 60 minutes, with three cycles of IPC lasting two minutes each. In this study, IPC performed with the same time span used by Dorsa et al [15] did not result in hepatic protection, obtaining results similar to the I/R group. However, there is still a lot of controversy in the literature on the outcome of remote protection of IPC.…”
Section: Discussionsupporting
confidence: 67%
“…This would be true when comparing these two studies evaluating IPC pulmonary action, since there was a difference in the method and this has been the greatest difficulty when comparing the numerous studies of IPC - the wide variation in the method used. The second question refers to the origin of ischemia: Dorsa et al [15] performed aortic clamping while Santos et al [16] and the present study used mesenteric ischemia. This factor may have some influence since in the aortic clamping, the harmful products of the I/R would spread to all the organs and tissues, whereas in the intestinal I/R, all blood is primarily drained to the liver, thus leading to increased toxic concentration of reactive oxygen species on this organ.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Recently, Dorsa et al [ 22 ] had demonstrated a protective effect of IPC on lung of rats undergoing aortic ischemia and reperfusion process. They have used also 30 minutes of ischemia and 60 minutes of reperfusion, but it was made by aortic occlusion, differently of our research.…”
Section: Discussionmentioning
confidence: 99%
“…Santos et al [ 4 ] demonstrated that the efficacy of this method is similar to the efficacy of ischemic preconditioning, and there is no statistically significant difference between the two. This technique is also able to protect tissues at a distance and can be applied in arteries distal to the primary ischemic process, which is effective as demonstrated by Dorsa et al [ 5 ] , and was thus called remote postconditioning.…”
Section: Introductionmentioning
confidence: 99%